M&A as an Entry model to United States IT market for Lenovo Company - Li, Yang (2008)
Once the concept of globalization came into the economic perspective, the world is deemed to change according to the globalization. Nowadays, it is very easy to realize the impacts of globalization brought to the way of doing business. Over the years, the World business environment in the more and more global market has received the dramatic changes (Welch and Luostarinen, 1988). Many powerful and large companies are not limited the local or domestic market, instead they are forced to the international market and indulged themselves in the competitive business environment. It is said that the phenomenon of outward investment for enterprises is the certain development trend under the rapid changing international market (Porter, 1986). On the one hand, the activities of outward investment for enterprises are normal strategies to utilize their existed domestic resources sufficiently and expand them into the oversea market (Horstmann and Markusen, 1996). It is regarded as the way of resource expansion according to the traditional FDI. However, on the other hand, according to the resource theories, it considered the outward investment as one reinforce or complementarily for the domestic lack resource. Through the way of outward investment, the enterprises could obtain maximum reinforces on the resource assignment. As well as according to assets-seeking perspective, the way of outward investment is also an effective complementary for strategic resources and the assets distributions in order to offset their competitive weakness in the global market.